Critical Analysis: Logical Fallacies in Students’ Debate Regarding Gender Issues - Syahputra, Mulyadi; Wahyuni, Sri; Rosdiana, Rosdiana; Mulyani, Mulyani; Aini, Riska Marlisa; Qamariah, Hijjatul; Sariakin, Sariakin (Jurnal Ilmiah Teunuleh, 2023)
Communication without logical fallacies is highly needed in the 21st century’s student’s skills. Many experts agreed that debate is an effective method to build students’ communication skills. The debate has now expanded from an ELT teaching method into a competitive platform to proliferate students’ critical thinking and communication. However, NUDC is one of the national scales of debate tournament that could represent the Indonesian students’ critical and communication skills. Considering that background in mind, this study was expected to identify the logical fallacies uttered by university students’ debate regarding gender issues. This study deployed a descriptive qualitative design. With a natural setting, the data were collected using the structured observation sheet in three phases, the debate observation without setting manipulation, the recorded debate was scripted and condensate, and analyzing the logical fallacies through the transcription. While the data analysis was conducted through data reduction, data condensation, and data conclusions. The data shows that there are seven logical fallacies uttered by the speakers in the debate about the gender issue. They are misleading euphemism, prejudicial language, an appeal to fear, an appeal to pity, straw man, hasty generalization, and a slippery slope. Besides, the speakers who uttered the logical fallacies were also presented.